(untitled) (Journal of Scientific Research, 2011)
The use of chemotherapeutic agents has been questioned for disease management in shrimp aquaculture due to the emergence of drug-resistant bacteria and enduring residual effects in the environments. Instead, microbial interventions in sustainable aquaculture have been proposed, and among them, the use of probiotics as an alternative to antibiotics has gained considerable attention. Earlier, we short-listed nineteen isolates out of ninety six bacteria, isolated from shrimp ghers of coastal areas of Bangladesh that exhibited antagonistic potential against pathogenic vibrios, and non-hemolytic property, presumably indicating their harmless behavior in mammalian system at least in vitro. This prompted us to study their cytotoxic effect in vivo using brine shrimp Artemia franciscana. Six isolates were found having higher lethal values compared with others. Four of them, identified as Pseudomonas and Bacillus spp. exhibited the lowest inhibition against Artemia and were considered safe. Further, in a co-culture experiment it was evident that the isolated probiotic bacteria were shown to outcompete the growth of pathogenic Vibrio harveyi due to their antagonistic properties. The probionts can now therefore be tested in culture environment of Bangladesh in order to understand the effectiveness of microbial control of bacterial diseases in shrimp aquaculture. Keywords: Probiotic bacteria; Food safety; Shrimp aquaculture; Vibrios. © 2011 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi:10.3329/jsr.v3i3.7750 J. Sci. Res. 3 (3), 659-668 (2011)